The speed of large-scale transformation of political and economic institutions : insights from (post-)transitional European Union countries - Šimić Banović, Ružica (Array, 2019)
This article compares the applicability of both the gradual and the shock therapy approach to reform implementation in large-scale change. Using quantitative data, it aims to provide more evidence for the lessons learned from post-socialist transformation. Hence it adds a theoretical and an empirical contribution to the body of literature on great transformations, focusing on their speed and theacceptability of related policy solutions. Despite the predominant inclination towards the gradualist approach to reforms in the initial transition years, economic indicators suggest that the bigbang reformers have demonstrated a superior performance over the last (few) decade(s). Still, the approach to (post-)transition processes should be multidimensional and include more than the speed of transformation and key economic indicators. Therefore, a quantitative analysis covers several aspects of socioeconomic change. The analysis of the quality of democracy, market economy, and management performance in post-socialist EU member states indicates that overthe last decade the countries that applied the shock therapy approach have performed significantly better in all these areas. This suggests that slow reformers are lagging behind in the development of democratic institutions and a modern market economy, and presumably have insufficient capacities to rapidly catch up with fast reformers.Further research on this topic should tackle the deep roots of socioeconomic development and path-dependent choices (reform speed included), proximity to Western countries, the possible effects of other specific circumstances (such as war), the importance of selected institutions on the performance of post-socialist non-EU member states, and other limitations.